OP0013 Effective Treatment Rapidly Improves both Disease Activity and Physical Activity in Early Rheumatoid Arthritis. (9th June 2015) - Konijn, N.; van Tuyl, L.; Boers, M.; Den Uijl, D.; Ter Wee, M.; Kerstens, P.; Voskuyl, A.; Nurmohamed, M.; van Schaardenburg, D.; Lems, W.
Abstract : Background: Regular physical activity (PA) has multiple health benefits, especially for patients with rheumatoid arthritis (RA) given their increased risk for osteoporotic fractures and cardiovascular diseases [1]. Combination therapy is a successful treatment for early RA with positive effects on disease activity and progression of joint damage. The effect of combination therapy on PA in early RA patients has not been studied before. Objectives: To investigate the longitudinal relationship between disease activity and PA in early RA patients during the first year of treatment with combination therapy. Methods: PA was measured with the Short QUestionnaire to ASsess Health-enhancing physical activity (SQUASH) at baseline, 13 weeks, 26 weeks, and 52 weeks after start of treatment in context of the COBRA-light trial [2]. The reported PA classified patients as meeting or not meeting the World Health Organization (WHO) PA guideline (cut off: 150 minutes of moderate-intense activity per week). Other measurements included the Disease Activity Score (44 joints; DAS). Since both treatment arms showed strong and similar effects on disease activity, results were analysed as one group with before-after analyses and generalized estimating equations (GEE). Results: In the current analyses, 140 patients (86% of trial population; 66% women, mean age 52 years, median disease duration 16 weeks) with complete data were included (Table 1 ). At entry, 69% of these patients met the WHO PA guideline, increasing to 90% at week 13, and remaining stable at 89% after one year (p<0.001). Mean DAS improved from 4.0 to 1.8 during the first year of treatment (p<0.001). In logistic GEE analyses, DAS decreases were significantly associated with PA increases (p=0.008). Patients with clinically relevant responses (expressed as minimal disease activity, EULAR good or ACR70 response) after one year of treatment were significantly more physically active compared to patients without such response. Conclusions: Early RA patients on combination therapy improve both disease activity and physical activity during the first year of treatment. References: Iversen et al., Int J Clin Rheumtol 2012; Ter Wee M et al., Ann Rheum Dis 2014. Disclosure of Interest: N. Konijn: None declared, L. van Tuyl: None declared, M. Boers: None declared, D. Den Uijl Grant/research support from: This research was performed within the framework of project T1-106 of the Dutch Top Institute Pharma, and was additionally funded by an unrestricted grant from Pfizer., M. Ter Wee: None declared, P. Kerstens: None declared, A. Voskuyl: None declared, M. Nurmohamed: None declared, D. van Schaardenburg: None declared, W. Lems Grant/research support from: This research was performed within the framework of project T1-106 of the Dutch Top Institute Pharma, and was additionally funded by an unrestricted grant from Pfizer